TSGΔ154-1054 splice variant increases TSG101 oncogenicity by inhibiting its E3-ligase-mediated proteasomal degradation - Chua, Huey-Huey (Oncotarget, 2016)
Tumor susceptibility gene 101 (TSG101) elicits an array of cellular functions, including promoting cytokinesis, cell cycle progression and proliferation, as well as facilitating endosomal trafficking and viral budding. TSG101 protein is highly and aberrantly expressed in various human cancers. Specifically, a TSG101 splicing variant missing nucleotides 154 to 1054 (TSGΔ154-1054), which is linked to progressive tumor-stage and metastasis, has puzzled investigators for more than a decade. TSG101-associated E3 ligase (Tal)- and MDM2-mediated proteasomal degradation are the two major routes for posttranslational regulation of the total amount of TSG101. We reveal that overabundance of TSG101 results from TSGΔ154-1054 stabilizing the TSG101 protein by competitively binding to Tal, but not MDM2, thereby perturbing the Tal interaction with TSG101 and impeding subsequent polyubiquitination and proteasomal degradation of TSG101. TSGΔ154-1054 therefore specifically enhances TSG101-stimulated cell proliferation, clonogenicity, and tumor growth in nude mice. This finding shows the functional significance of TSGΔ154-1054 in preventing the ubiquitin-proteasome proteolysis of TSG101, which increases tumor malignancy and hints at its potential as a therapeutic target in cancer treatment.